Molecular identification of Sarcocystis aucheniae in the wild South American camelid Vicugna vicugna - Wieser, Sara Nathaly (2024)
Vicuñas (Vicugna vicugna) are wild South American camelids (SACs) protected by law in Argentina, and information on pathogens that infect them is scarce. In this study, an adult vicuña found dead in the province of Salta was examined, and evidence of infection by Sarcocystis sp. protozoans was sought. Infection of skeletal muscles by S. aucheniae, with the production of macroscopic sarcocysts, a disease known as SAC sarcocystosis, has been described in the other three SACs - llamas, alpacas, and guanacos - but its occurrence in vicuñas has so far remained unknown. In the analyzed individual, many macroscopic cysts compatible with S. aucheniae were found upon necropsy in the muscular tissue of the neck and diaphragm. Analysis of 18 S rRNA and cytochrome c oxidase subunit 1 (cox-1) gene sequences by BLAST searches and construction of phylogenetic trees demonstrated that the etiological agent was S. aucheniae. Our results show for the first time that vicuñas act as intermediate hosts in the life cycle of this parasite. In addition, this study provides the first cox-1 sequences for S. aucheniae isolates from the four SAC species acting as intermediate hosts and suggests that this marker could be useful for genotypification of this parasite species. The impact of SAC sarcocystosis on the health, well-being, and fitness of vicuñas, and the relevance of vicuña infections in the epidemiology of S. auchaniae, remain to be elucidated.